Sex-Specific Relationship of Childhood Adversity With Gray Matter Volume and Temperament - Dragan, Wojciech Łukasz; Jednoróg, Katarzyna; Marchewka, Artur (Frontiers in Behavioral Neuroscience, 2019)
Background: To date, many studies have attempted to show a relationship between potentially harmful experiences in childhood and gray matter volume (GMV) in specific brain areas. These studies managed to identify several affected regions, yet most of them neglected the influence of sex or the occurrence of mental health problems. Furthermore, little is known about mechanisms linking childhood adversity (CA) and temperamental traits as plausible endophenotypes of psychopathology. Objective: The present study addresses these two issues by trying to identify sex-specific relationships between CA and brain volumes as well as to show the role of the latter in predicting temperament scores. Method: 48 people (23 women) without anxiety or affective disorders participated in this study. Childhood adversity was measured using the Childhood Questionnaire and temperament was measured with the use of the BIS-BAS Scales. Whole-brain MR imaging was performed to identify GMV differences. Results: In women, we identified negative relationships between childhood adversity and GMV in the left inferior parietal lobule, right cerebellum, and right precentral gyrus. In men, we found a negative correlation between childhood adversity and GMV in the right fusiform gyrus. We also identified sex-specific relationships between childhood adversity and temperament traits. Conclusions: The results of our study suggest a sex-specific pattern in the relationship between early adverse experiences and brain structure. The results can also help explain the role that temperament plays in the relationship between CA and the risk of psychopathology.